2012
DOI: 10.5812/hepatmon.6025
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Persistence of Seroprotection by Hepatitis B Vaccination in Healthcare Workers of Southern Italy

Abstract: BackgroundThe impact of hepatitis B virus (HBV) vaccination campaigns on HBV epidemiology needs to be evaluated, in order to assess the long-term immunity offered by vaccines against HBV.ObjectivesTo evaluate the current status of anti-HBV vaccine coverage among healthcare workers (HCWs) in Southern Italy, and to determine the long-term persistence of antibodies to hepatitis B surface antigens (anti-HBs) in such a cohort of subjects.Patients and MethodsA longitudinal, retrospective seroepidemiological survey w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 39 publications
2
13
1
Order By: Relevance
“…The current study did not find any association between age and adequate response; these results were in agreement with those of other studies conducted in Iran, Italy and South Asia (20,21,28,29). Some studies in Japan and Europe found that anti-HBs level decreases with age (26,30).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The current study did not find any association between age and adequate response; these results were in agreement with those of other studies conducted in Iran, Italy and South Asia (20,21,28,29). Some studies in Japan and Europe found that anti-HBs level decreases with age (26,30).…”
Section: Discussionsupporting
confidence: 82%
“…According to the current study results, 5.6% of HCWs did not develop a protective level after the first series, and inadequate immunity after the second series of vaccination was less than 1%, which was lower than those of similar studies in Poland (12.2%), Sri Lanka (9.9%) and Italy (11.6%) (20)(21)(22).…”
Section: Discussioncontrasting
confidence: 47%
“…Protective serum titers of anti-HBs (greater than 10 IU/L) develop in 95%-99% of healthy infants, children [101,102] and young adults [103] . Many studies have demonstrated that HBV vaccination has dramatically decreased the HBV chronicity rates and HBV-related complications [7] .…”
Section: Genotypes' Impact On Prophylaxis Measuresmentioning
confidence: 99%
“…The immunization of workers reduces their susceptibility to infection and infections' number. Long-term immunity offered by vaccines against HBV was recently reported in 50% of health workers 30 years after vaccination [7]. …”
Section: Introductionmentioning
confidence: 99%